Using Carbon Isotope Discrimination to Assess Genotypic Differences in Drought Resistance of Parental Lines of Common Bean - Sanz-Saez, Alvaro; Maw, Michael J.W.; Polania, Jose A.; Rao, Idupulapati M.; Beebe, Stephen E.; Fritschi, Felix B. (Wiley, 2019)
Accurate assessment of crop water uptake (WU) and water use efficiency (WUE) is not easy under field conditions. Carbon isotope discrimination (Δ13C) has been used as a surrogate of WUE to examine crop yield responses to drought and its relationship with WU and WUE. A 2-yr study was conducted (i) to characterize genotypic variation in Δ13C, grain yield, and other physiological parameters in common bean (Phaseolus vulgaris L.) parental lines, and (ii) to examine the relationships between grain Δ13C, shoot Δ13C, and grain yield under well-watered and terminal drought stress conditions. All measured plant traits were strongly influenced by water availability, and genotypic differences in grain yield, shoot Δ13C, and grain Δ13C were found in both watered and terminal drought stress environments. The parental lines were classified into two drought adaptation groups, drought resistant and drought sensitive, based on a yield drought index. High yields under drought conditions were related to (i) greater water uptake, as indicated by high Δ13C in genotypes previously shown to have deeper roots (e.g., SEA 5 and BAT 477), and (ii) increased WUE, denoted by lower Δ13C and greater pod harvest index (PHI) (e.g., SER 16). Coupling of Δ13C measurements with measured yield and yield components analyses, such as PHI, provided an avenue to distinguish different physiological traits among drought resistant genotypes underlying adaptation to water deficit stress